Reproductive cycle of Poptella paraguayensis (Eingenmann, 1907), (Characiformes, Characidae - Saia Branca), in the Paraguay river, City of Cáceres-MT, Brazil (Research, Society and Development, 2021)
The Characidae family and subfamily Stethaprioninae are a group of small fish. The species Poptella paraguayensis (Eingenmann, 1907) popularly known as "white skirt" is characterized by the presence of a longitudinal silver band just above the lateral line and a black stripe underneath. The reproduction was characterized P. paraguayensis, specifically aspects related to spawning flood pulse in system Bays Caiçara, Paraguay River, Pantanal. In total 1612 specimens were collected between the months of September 2005 to September 2007, called Cycle I (2005-2006) and Cycle II (2006-2007), both in Caiçara Lower Bay (BCI) as the Caiçara Superior Bay (BCS). For the collections of fish we used nylon net, trawl, cast nets and gill nets. The fish were fixed in 4% formalin for 72 hours and stored in 70% alcohol solution. Once gutted, the digestive tracts removed, identified and defined sex and reproductive stage. In total, 1612 specimens were sampled and the flood period is the period with the highest percentage of individuals in the stage of mature gonads for reproduction. Thus, it is noteworthy that P. paraguayensis is a base species of the food chain and widely exploited as bait among fishermen and this study demonstrates the hydrological periods in which the species reproduces.